Ecosystem, spatial and trophic dimensions of niche partitioning among freshwater fish predators - Říha, Milan; Vejřík, Lukáš; Rabaneda-Bueno, Rubén; Jarić, Ivan; Prchalová, Marie; Vejříková, Ivana; Šmejkal, Marek; Blabolil, Petr; Čech, Martin; Draštík, Vladislav; Holubová, Michaela; Jůza, Tomáš; et al. (Movement ecology, 2025)
BACKGROUND: Niche partitioning allows species to diversify resource utilisation and space allocation and reduce interspecific competition. Variations in abiotic and biotic conditions in different ecosystems may further influence resource availability and habitat utilisation, potentially reducing competition. The aim of this study is to investigate the effects of environmental variation on spatial and trophic niche overlap between two freshwater apex predators, the northern pike (Esox lucius) and the European catfish (Silurus glanis), in three different water bodies. METHODS: We used fine-scale acoustic telemetry to assess the spatial niche overlap of pike and catfish, analyzing their spatial and habitat use in relation to the thermocline and their presence in benthic versus open-water habitats. Stable isotope analysis (SIA) was used to quantify trophic niche overlap and dietary differences between the species. We compared the habitat use, spatial niche width and overlap, and trophic differentiation among waterbodies to determine how environmental conditions influence predator interactions. RESULTS: During summer, pike and catfish primarily occupied benthic habitats above the thermocline across all waterbodies and diel periods. However, catfish more frequently used open water above the thermocline, while pike were more often present in both open water and benthic habitats below it. While this general pattern of habitat use was consistent, its extent varied among lakes, suggesting that local environmental conditions shape species-specific habitat selection. Despite these variations, the species exhibited substantial spatial overlap, though its magnitude fluctuated across waterbodies and diel periods. Catfish occupied a broader spatial niche in two waterbodies, while pike had a broader niche in one. Across all lakes, catfish consistently maintained a broader trophic niche than pike. However, pike exhibited higher trophic overlap with catfish than vice versa, with nearly complete overlap in one lake and substantial but incomplete overlap in others. This suggests that pike relies more heavily on shared prey resources, while catfish exploits a broader range of food sources beyond those used by pike.These patterns were primarily driven by the position of the thermocline, prey availability, structural complexity and the greater foraging plasticity of catfish, highlighting the environmental dependence of niche partitioning in these predators. CONCLUSIONS: Our findings demonstrate that spatial and trophic niche overlaps between pike and catfish are highly context-dependent, shaped by abiotic conditions, prey availability, and species-specific foraging strategies. This study highlights the importance of integrating spatial and trophic analyses to understand predator interactions in aquatic ecosystems.
Keywords: Niche partitioning; Stable isotopes; Acoustic telemetry; Interspecific competition; Dietary plasticity; Spatial niches; Predator interactions; Environmental variation; Aquatic ecosystems; Trophic niches; Resource utilization